Creativity for a new curriculum : 5-11 - Newton, Lynn D., 1953- (London : Routledge, 2012)
'Creativity for a New Curriculum: 5-11 provides an account of what creativity really means in the context of children's learning in the primary school, and describes in practical terms what teachers can do to foster it. At a time of curriculum development and change, it focuses on the opportunity to build a new curriculum that is inclusive of creativity and is fit for the twenty-first century. The value of fostering creative thinking and problem solving abilities in education is widely recognised for its capacity to confer an independence and ability to function effectively in life. As such, encouraging children to be creative thinkers and problem solvers should be an integral part of everyday teaching and learning across all subjects. Building upon the research and practices of a group of educators studying creativity across the curriculum and coordinated by the author, this book provides primary teachers and trainee teachers with easy to understand explanations of what creativity means in the context of the subjects of the curriculum for young children. It introduces ideas for how to nurture and support it, and explores issues associated with fostering it, such as assessment. Chapters cover areas including: - A brief history of creativity and pedagogy, including common misconceptions - Strategies for creative learning as well as creative teaching - Creativity in English - Creativity in Mathematics - Creativity in Science and Design and Technology - Creativity in Art and Music - Creativity in History and the Humanities - Creativity in ICT - International perspectives on creativity'--
Includes bibliographical references and index.
Keywords: Creative thinking -- Study and teaching (Elementary).; Problem solving -- Study and teaching (Elementary).; Curriculum change